Analisis Penataan Self-Portrait Berbasis Seni - Sarwo Nugroho; Ichsan Ichsan; Fa’iqah Salsabil Qadiriyyah (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
The aim of this study is to describe the development of an innovative art-based analytical method in portrait methodology. This article exemplifies how forms of multimodal analysis can be integrated into portraiture frameworks and provides a fluid qualitative "recipe" for researchers interested in applying the portrait method. The study described in this article examines the teaching of vulnerability and resilience using poetry and the visual arts as integral elements of the portraiture process. Portraiture is a qualitative, feminist, artistic method based on ethnography and phenomenology for depicting, understanding and interpreting complex human experiences. This study leads to the methodological development of the three steps of analysis in the portrait process: Sketch, poetic expression and artistic expression. This phase of data analysis emphasizes the richness of the methodological snapshot and focuses on engaging the researcher in creative, intuitive and associative processes. – The studies presented in this article are examples of qualitative research that pushes methodological boundaries and focuses on the role of intuition, association, and creativity in research